Flow modulation epitaxy of hexagonal boron nitride. (13th August 2018) - Chugh, D; Wong-Leung, J; Li, L; Lysevych, M; Tan, H H; Jagadish, C
Abstract: Growth of hexagonal boron nitride (hBN) layers on 2″ sapphire substrate using metal organic vapour phase epitaxy is reported here, where we compare the growth under continuous flow and flow modulation (FM) schemes. hBN films grown under the continuous flow regime exhibit low growth rate and rough surface profiles due to severe parasitic reactions between precursor molecules, which are suppressed by adopting a FM scheme. We also observe spontaneous delamination of hBN films from the substrate when immersed in a water bath and attribute this to be due to relaxation of compressive stress in the films, which was further corroborated using Raman spectroscopy. Carbon is identified as a major impurity which gets incorporated as boron carbide under FM growth and results in large sub-bandgap fluorescence in the range of 1.77–2.25 eV. Overall, hBN films deposited using the FM scheme at low growth rate (~2–3 nm h −1 ) exhibited the best characteristics in the present study, which will be suitable for applications such as van der Waals epitaxy and 2D hetero-structure devices.